Seismic Performance of RC Buildings with Different Positions of Lift Core Wall and Added Shear Walls - Baral, Bikash; Suwal, Rajan (Journal of Advanced College of Engineering and Management, 2023)
Nepal is situated in an area with considerable seismic activity. It is important to choose structural systems that can withstand the lateral loads. In a dual system of reinforced concrete structures, the placement of shear walls optimally increases the stiffness of the buildings. The lateral rigidity of RC buildings may be improved by strategically placing lift core walls. Buildings would be more useful if they had easy access to an elevator and stairs. Torsional irregularity in buildings would be caused by the lift core wall's eccentric location. For these kinds of structures, a bidirectional seismic excitation study is required. In design, IS 1893:2016 is applied. Drift limitations are obtained from FEMA 356 2000 for different damage conditions and median displacement values are taken as per HAZUS 4.2 SP3. This research work presents the vulnerability due to eccentric positioning of lift core in symmetrical reinforced concrete frame. The torsional irregularities are needed to be removed with optimum positioning of extra shear walls. The reduction in vulnerability of buildings due to added walls is also studied.